2001
DOI: 10.1159/000054034
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of HPV-16 E5 Protein in Squamous Neoplastic Changes in the Uterine Cervix

Abstract: To investigate the expression of human papillomavirus type 16 (HPV-16) E5 protein in squamous neoplastic changes in the uterine cervix, the specific E5 antibody was generated and used to identify the expression of E5 protein in 40 cases of HPV-16-positive tissues and 5 previously identified HPV-negative normal cervical tissues. The results revealed that E5 protein was primarily expressed in the lower third of the epithelium in low-grade squamous intraepithelial lesions (SILs) and throughout the whole epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The E5 protein has been detected in lesions induced by BPV where it localises to the basal cell layer and to differentiated epithelial cells supporting genome amplification [17]. In cervical biopsies caused by HPV16, one report has shown the protein to be present in the lower epithelial layers, but not specifically in basal cells [21]. As with E2, there are only a limited number of studies that have investigated E5 distribution in vivo, and it is difficult to be certain as to its precise expression pattern.…”
Section: Amplification Of Viral Genomesmentioning
confidence: 99%
“…The E5 protein has been detected in lesions induced by BPV where it localises to the basal cell layer and to differentiated epithelial cells supporting genome amplification [17]. In cervical biopsies caused by HPV16, one report has shown the protein to be present in the lower epithelial layers, but not specifically in basal cells [21]. As with E2, there are only a limited number of studies that have investigated E5 distribution in vivo, and it is difficult to be certain as to its precise expression pattern.…”
Section: Amplification Of Viral Genomesmentioning
confidence: 99%
“…(18,19,20) Although the E5 ORF is deleted in advanced cervical lesions, it is believed that the encoded protein actively contributes during the early phases of carcinogenesis, making E5 along with E6 and E7 particular targets of interest in cervical cancer prevention and treatment. (21) HR-HPV E5 has been shown to cooperate positively with E6 and E7 in cancer progression to enhance their transformation activity in the early stages of precancerous lesions. (21) It has also been observed that E5 exhibits cell transformation potential when expressed alone; however, this transformation potential is weak.…”
mentioning
confidence: 99%
“…(21) HR-HPV E5 has been shown to cooperate positively with E6 and E7 in cancer progression to enhance their transformation activity in the early stages of precancerous lesions. (21) It has also been observed that E5 exhibits cell transformation potential when expressed alone; however, this transformation potential is weak. (20) In this study, we focused on examining the effects of HPV-18 oncoproteins on certain hallmarks of cancer in HaCaT cells.…”
mentioning
confidence: 99%
“…Although we are not able to show whether the EGFR is required for these activities we did show that E5 activates the MAPK pathway consistent with E5 enhancing ligand dependant EGFR activation. Forty percent of human cancers do not express E5 protein, which correlates with the integration of the HPV genome into the host genome (34). In our studies, there was no appreciable effect of E5 on overall disease severity in mice that express both E6 and E7.…”
Section: Discussionmentioning
confidence: 99%